"Expectations gap" and the Whole Complex of Engagements, Provided by Certified Auditors - Shalimova, N.; Шалімова, Н. С. (National Aviation University, 2020)
The peculiarities of the "gap in expectations" in the audit are determined, taking into account the whole set of engagements that can be performed by certified auditors. It is proved that the lack of understanding of the features and differences between different types of engagements leads to the formation of unsubstantiated expectations and dissatisfaction with the results of the work of auditors. Визначено особливості прояву «розриву в очікуваннях» в аудиті за умови врахування всього комплексу завдань, що можуть виконуватися сертифікованими аудиторами. Доведено, що саме недостатність розуміння особливостей та відмінностей між різними видами завдань призводить до формування необґрунтованих очікувань та невдоволеністю результатами роботи аудиторів.
Keywords: audit; gap in expectations; assurance engagement; audit engagements; International Standards